2021
DOI: 10.1021/acs.biomac.1c00242
|View full text |Cite
|
Sign up to set email alerts
|

Non-Covalent Carrier Hydrophobicity as a Universal Predictor of Intracellular Protein Activity

Abstract: Over the past decade, extensive optimization of polymeric cell-penetrating peptide (CPP) mimics (CPPMs) by our group has generated a substantial library of broadly effective carriers which circumvent the need for covalent conjugation often required by CPPs. In this study, design rules learned from CPPM development were applied to reverse-engineer the first library of simple amphiphilic block copolypeptides for non-covalent protein delivery, namely, poly­(alanine-block-arginine), poly­(phenylalanine-block-argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 103 publications
0
30
0
Order By: Relevance
“…Among the abovementioned polymerization methods, ROMP is the most suitable polymerization route because ROMP reactions proceed rapidly in the presence of air-stable and functional groups of tolerant ruthenium Grubbs catalysts in mild conditions and allow the acquisition of different functional polymeric materials with desired structure and composition [10][11][12][13]. The employment of ROMP for the preparation of polymeric materials for different biomedical applications is presented in recent articles [14][15][16]. Hango et al developed oxanorbornene-based block copolymers capable of effective intracellularly protein delivery [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the abovementioned polymerization methods, ROMP is the most suitable polymerization route because ROMP reactions proceed rapidly in the presence of air-stable and functional groups of tolerant ruthenium Grubbs catalysts in mild conditions and allow the acquisition of different functional polymeric materials with desired structure and composition [10][11][12][13]. The employment of ROMP for the preparation of polymeric materials for different biomedical applications is presented in recent articles [14][15][16]. Hango et al developed oxanorbornene-based block copolymers capable of effective intracellularly protein delivery [14].…”
Section: Introductionmentioning
confidence: 99%
“…The employment of ROMP for the preparation of polymeric materials for different biomedical applications is presented in recent articles [14][15][16]. Hango et al developed oxanorbornene-based block copolymers capable of effective intracellularly protein delivery [14]. In the paper by Kockelmann et al, 2020, it is reported that poly(norbornene)-based nanogels can be utilized as drug delivery agents in anticancer immunotherapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…S26†). 29,40,48,49 Cargo binding appeared to be driven by the polymer repeat unit to protein ratio ( i.e. , mass concentration of polymer in the system) rather than PTDM DP.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study using the same reporter Jurkat T cell line, the polymers MePh 10 - b -dG 5 , dMe 10 - b -dG 5 , and dPh 5 - b -dG 5 yielded recombination rates of 25%, 50%, and 45%, respectively (560 nM, 5 : 1). 29 In a different human T cell line, MePh 9 - b -dG 5 reached 70% using Cre and 90% using a Tat-Cre conjugate, which facilitates some cellular entry on its own (125 nM, 10 : 1). 42 Two additional reports in this cell line demonstrated the abilities of dPh 5 - b -dG 5 and dPh 5 - grad -dG 5 (gradient architecture) to edit up to 70% (Cre) and 90% (Tat-Cre) of cells (100–150 nM, 5 : 1–10 : 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation